Early experience in endoscopic management of massive intraventricular hemorrhage with literature review - Idris, Zamzuri; Raj, Jason; Abdullah, Jafri (Asian Journal of Neurosurgery, 2014)
Massive intraventricular hemorrhage (IVH) is nearly always associated with hydrocephalus and is often treated with prolonged external ventricular drainage (EVD); however this procedure can lead to bacterial ventriculitis and meningitis, which can worsen the clinical outcomes. Endoscopic burr hole surgery to remove the hematomas in lateral and third ventricles is an alternative treatment option. We describe the surgical techniques and benefits of endoscopic surgery for acute massive IVH in four patients and discuss the current published literature-related to this condition. Four patients were treated endoscopically for massive IVH. Three patients presented with secondary IVH due to vascular malformation, tumoral bleed and chronic hypertension, while one case presented as massive primary IVH. Endoscopic wash out and removal of hematomas was normally performed together with an endoscopic third ventriculostomy. Recombinant factor VIIa was only administered prior to surgery for IVH secondary to vascular malformation and for cases with postoperative rebleeding which required second endoscopic surgery. Weaning from ventilator and EVD commenced on day 4 postoperatively. All treated patients recovered and did not require further shunt surgery. Good outcomes obtained may be related to early removal of hematomas, creation of new cerebrospinal fluid diversion pathway after thorough wash-out, early weaning from ventilator and EVD. Endoscopic surgery is beneficial in treating poor grade IVH with Graeb score of more than 6.
Keywords: Endoscopy; factor VIIa; Graeb score; hydrocephalus; intraventricular haemorrhage